Photo catalytic degradation of Indigo carmine in aqueous media using Nano crystalline zirconia by solid state method: synthesis and characterization (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The (ZrO2/rGO) Nano composite photo catalytic was made by solid state technique at varied ratios (1:2,2:1,3:4) and calcination at 700 oC for 20 hours in this work. ZrO2/rGO NC was synthesized. FTIR, XRD, UV-Visible, FESEM, Bet, and Bjh were used to examine the prepared powder. The degradation indigo carmine dye (m.f. C16H8N2Na2O8S2) to wavelength of the solution of max(608) nm was projected under high pressure mercury lamp (HPML) OSRAM (125) watts to Nano partials (ZrO2) by solid state method and calcination at temperature 700Co for 20h. The conclusion improved the catalyst's mass, early concentration for (ZrO2/rGO), pH effect, and temperature effect. Microscopy studies revealed that the granules produced for the composite were of a consistent size .